Efektivitas Kegiatan Humas AK UPN Radio Pada Event Radioactive With Raye Sabrina - Ahmad Shidqi Haetami; Sintya Christianti, Dyva Claretta; Ahimsa Adi (CV. ITTC INDONESIA, 2022)
This study aims to find out how the effectiveness of public relations activities for AK UPN Radio and find out the Public Relations Audit as a public relations function at the AK UPN Radio's â€œRadioactiveâ€ event. The research method that we used is qualitative research with in-depth interviews. The results of this study indicate that with the Pyramid Model of PR method it can be seen that the AK UPN Radio public relations team carried out their duties effectively and systematically in attracting listenersâ€™ interest and reaching a wider audience, not only within the university scope but also this public relations program managed to penetrate even beyond city of Surabaya.